A common analysis framework for simulated streaming-video networks - Mulumba, Patrick (Rhodes University, Faculty of Science, Department of Computer Science, 2009)
Distributed media streaming has been driven by the combination of improved media compression techniques and an increase in the availability of bandwidth. This increase has lead to the development of various streaming distribution engines (systems/services), which currently provide the majority of the streaming media available throughout the Internet. This study aimed to analyse a range of existing commercial and open-source streaming media distribution engines, and classify them in such a way as to define a Common Analysis Framework for Simulated Streaming-Video Networks (CAFSS-Net). This common framework was used as the basis for a simulation tool intended to aid in the development and deployment of streaming media networks and predict the performance impacts of both network configuration changes, video features (scene complexity, resolution) and general scaling. CAFSS-Net consists of six components: the server, the client(s), the network simulator, the video publishing tools, the videos and the evaluation tool-set. Test scenarios are presented consisting of different network configurations, scales and external traffic specifications. From these test scenarios, results were obtained to determine interesting observations attained and to provide an overview of the different test specications for this study. From these results, an analysis of the system was performed, yielding relationships between the videos, the different bandwidths, the different measurement tools and the different components of CAFSS-Net. Based on the analysis of the results, the implications for CAFSS-Net highlighted different achievements and proposals for future work for the different components. CAFSS-Net was able to successfully integrate all of its components to evaluate the different streaming scenarios. The streaming server, client and video components accomplished their objectives. It is noted that although the video publishing tool was able to provide the necessary compression/decompression services, proposals for the implementation of alternative compression/decompression schemes could serve as a suitable extension. The network simulator and evaluation tool-set components were also successful, but future tests (particularly in low bandwidth scenarios) are suggested in order to further improve the accuracy of the framework as a whole. CAFSS-Net is especially successful with analysing high bandwidth connections with the results being similar to those of the physical network tests.
Keywords: Computer networks -- Management; Streaming video; Mass media -- Technological innovations